2010
DOI: 10.1093/rheumatology/keq163
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Angiopoietin-Tie ligand-receptor system with a novel splice variant of Tie1 reduces the severity of murine arthritis

Abstract: Our data demonstrate that the Ang-Tie ligand-receptor system is dysregulated in CIA. Tie1-751, a novel splice variant of the Tie1 receptor, inhibits Ang1/VEGF signalling, suggesting that Ang inhibition may be of therapeutic benefit in inflammatory arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…A significant increase in transcript levels could be observed on day 8 for all genes, with mRNA levels gradually decreasing on day 12 (mean clinical score ± SEM of the analysed paws 1.67 ± 0.38), which is consistent with the array results. We have previously reported that expression of Ang-1 , Ang-2 , tyrosine kinase with immunoglobulin-like and EGF-like domains ( Tie )-1 and Tie-2 increases as arthritis progressed, peaking on day 8 of disease [33]. Of these, Ang-2 and Tie-2 showed modest changes (below 2-fold) on the array, whereas Ang-1 increased 2.7-fold on day 8 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant increase in transcript levels could be observed on day 8 for all genes, with mRNA levels gradually decreasing on day 12 (mean clinical score ± SEM of the analysed paws 1.67 ± 0.38), which is consistent with the array results. We have previously reported that expression of Ang-1 , Ang-2 , tyrosine kinase with immunoglobulin-like and EGF-like domains ( Tie )-1 and Tie-2 increases as arthritis progressed, peaking on day 8 of disease [33]. Of these, Ang-2 and Tie-2 showed modest changes (below 2-fold) on the array, whereas Ang-1 increased 2.7-fold on day 8 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study we have shown that the expression of Ang-1 , Ang-2 , Tie-1 and Tie-2 mRNA is significantly higher in arthritic tissue of CIA mice, and that the application of a splice variant of TIE-1 ameliorates disease severity, reduces synovial vascularisation and bone destruction [33]. Our angiogenesis array identified Ang-1 as up-regulated by more than 2-fold, whereas Ang-2 was increased by only 1.6-fold on day 8 of CIA.…”
Section: Discussionmentioning
confidence: 99%
“…Although Tie1 is important for embryonic vessel development, its expression is also increased during pathologic conditions in the adult (14)(15)(16). Recent studies have indicated expression of Tie1 in inflammatory tissue of rheumatoid arthritis and osteoarthritis patients (17,18). Additionally, overexpression of Tie1 augmented the inflammatory markers VCAM-1, ICAM-1, and E-selectin (19).…”
Section: Introductionmentioning
confidence: 99%
“…5 8 22 23 Expression of Ang1, Ang2 and their receptor Tie2 are significantly increased in progression of collagen induced arthritis (CIA), and Tie2 blockade ameliorates bone destruction. 24 25 Recently, we demonstrated that Tie2 mediates Toll-like receptor-2 induced angiogenesis in Rheumatoid arthritis (RA). 26 The Notch signalling pathway plays a pivotal role in vascular development, cell-cell communication, cell fate decisions.…”
Section: Introductionmentioning
confidence: 99%